New Index for Evaluation of Oral Glucose Tolerance Test Results. Issue 5853 (10th March 1973) - Billewicz, W. Z.; Anderson, J.; Lind, T.
Abstract : A simple numerical index is presented which describes the shape of an oral glucose tolerance response curve and appears to be a measure of the efficiency of homeostatic control. It is unaffected by the laboratory method of glucose estimation, the site of blood sampling, the amount of glucose given, and whether or not the patient has fasted overnight. The index satisfactorily differentiates clinically diabetic from non-diabetic individuals and seems to provide a sensitive method of describing small changes in glucose homeostatic control such as might occur, for example, in pregnancy.